Innate PD-L1 limits T cell mediated adipose tissue inflammation - Schwartz, Christian; Schmidt, Viviane; Deinzer, Andrea; Hawerkamp, Heike C.; Hams, Emily; Bayerlein, Jasmin; Roeger, Ole; Bailer, Moritz; Krautz, Christian; El Gendy, Amr; Elshafei, Moustafa; Hogan, Andrew E.; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
Obesity has become a major health problem in the industrialized world. Immune regulation plays an important role in adipose tissue homeostasis; however, the initial events that shift the balance from a noninflammatory homeostatic environment toward inflammation leading to obesity are poorly understood. Here, we report a role for the costimulatory molecule programmed death-ligand 1 (PD-L1) in the limitation of diet-induced obesity. Functional ablation of PD-L1 on dendritic cells (DCs) using conditional knockout mice increased weight gain and metabolic syndrome during diet-induced obesity, whereas PD-L1 expression on type 2 innate lymphoid cells (ILC2s), T cells, and macrophages was dispensable for obesity control. Using in vitro cocultures, DCs interacted with T cells and ILC2s via the PD-L1:PD-1 axis to inhibit T helper type 1 proliferation and promote type 2 polarization, respectively. A role for PD-L1 in adipose tissue regulation was also shown in humans, with a positive correlation between PD-L1 expression in visceral fat of people with obesity and elevated body weight. Thus, we define a mechanism of adipose tissue homeostasis controlled by the expression of PD-L1 by DCs, which may be a clinically relevant finding with regard to immune-related adverse events during immune checkpoint inhibitor therapy.<br
CRIS-Team WoS Importer:2022-03-11